2015
DOI: 10.1017/s1092852915000826
|View full text |Cite
|
Sign up to set email alerts
|

Treating to target in major depressive disorder: response to remission to functional recovery

Abstract: Treating to target in chronic diseases [e.g. Major Depressive Disorder (MDD)] fosters precision, consistency, and appropriateness of treatment selection and sequencing. Therapeutic target definitions/endpoints in MDD should satisfy patient-, provider-, and societal expectations. Functional recovery in depression and return to both physical and mental health are the overarching therapeutic objectives. Treating to target in MDD implies multidimensional symptomatic remission, with a particular emphasis on cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 118 publications
2
52
0
1
Order By: Relevance
“…While both symptomatic and functional improvement are important components of full recovery, 21,23,[35][36][37][38][39][40] and may be linked, as demonstrated in several studies, 23,[35][36][37][38] they are not necessarily always coincident. 21,23,[35][36][37][40][41][42][43] The observation that functional recovery often lags behind symptomatic or syndromal recovery 41 may account for this lack of coincidence in the components of recovery.…”
Section: Madrs <= 12 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…While both symptomatic and functional improvement are important components of full recovery, 21,23,[35][36][37][38][39][40] and may be linked, as demonstrated in several studies, 23,[35][36][37][38] they are not necessarily always coincident. 21,23,[35][36][37][40][41][42][43] The observation that functional recovery often lags behind symptomatic or syndromal recovery 41 may account for this lack of coincidence in the components of recovery.…”
Section: Madrs <= 12 Andmentioning
confidence: 99%
“…21,23,[35][36][37][40][41][42][43] The observation that functional recovery often lags behind symptomatic or syndromal recovery 41 may account for this lack of coincidence in the components of recovery. Findings from this analysis indicated that there was a moderately high level of concordance between symptomatic remission and functional remission at the endpoints of both the core (77.9%) and extension (65.9%) studies.…”
Section: Madrs <= 12 Andmentioning
confidence: 99%
“…Understanding the importance of capturing varying domains/dimensions of cognitive function has a major role in improving MBC as functional outcomes can vary, dependent on impairment and/or improvement of varying domains/dimensions 9. An attribute of a screening/measurement tool for cognition in MDD is its ability to detect deficits across one or more of the domains known to be affected in MDD.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement-based care (MBC) improves treatment outcomes in chronic medical disorders and provides opportunities to increase precision, consistency and appropriateness of care 9. As such, given the impact of MBC, the appropriateness and suitability of the tools used is important.…”
Section: Introductionmentioning
confidence: 99%
“…At a minimum, societal changes should inform how the issue of excess/premature mortality in SMI is framed, understood, and addressed, as advances in science and technology are apparently benefiting only the mentally healthy part of the population. 7 A commitment to first recognizing and then addressing the problem of excess/premature mortality in SMI is needed from all actors, from healthcare policy makers through healthcare providers to patient and peer advocacy groups.…”
mentioning
confidence: 99%